One goal: Health for all; Post-COVID public health initiatives - Thomas Mathew (Wolters Kluwer Medknow Publications, 2023)
WHO's theme on its 75th year, "Health for All", is both appropriate and meaningful on account of the unfinished agenda of primary health care (PHC), the Sustainable Development Goals, and the aftermath of the COVID-19 pandemic. The Kerala experience of the pandemic amply demonstrated that the application of these PHC principles helped to address diverse aspects of physical, mental, and social dimensions. The need for 'internalization' of One Health principles and operational strategies cannot be over-emphasized.